Canopy architecture and leaf nitrogen distribution of rice (Oryza sativa L.) under chronic soil water deficit - Okami, M.; Kato, Y.; Yamagishi, J. (Wiley, 2016)
The development of vertical gradients of specific leaf nitrogen (SLN) in accordance with light gradients within a canopy is important for maximising resource‐use efficiency. In this study, we aimed to clarify the effect of chronic soil water deficit on the SLN gradient in rice. In a series of field experiments, SLN gradients of an indica cultivar and a tropical japonica cultivar were investigated under chronic soil water deficit. As a result, SLN gradient of an indica cultivar tended to be more uniform than that of a tropical japonica cultivar during the recovery period after dry spells under aerobic conditions: an indica cultivar distributed much N in shaded leaves while a japonica cultivar enhanced the SLN in the upper layers. We conclude that vertical gradient of SLN of indica cultivars becomes less optimal for photo‐assimilation under chronic soil water deficit, although they can take‐up sufficient amounts of N. This would be attributable to the rapid increase in tiller number upon rainfall or irrigation and prolonged tillering period for their recovery growth, leading to a more compact canopy architecture. The tillering habit in the current indica irrigated rice cultivars would be associated with the response of SLN gradients to chronic soil water deficit.